The mechanism of action of Russian propolis ethanol extracts against two antibiotic‐resistant biofilm‐forming bacteria. (February 2016) - Bryan, J.; Redden, P.; Traba, C.
Abstract: The interaction between antibiotic‐resistant Staphylococcus aureus and antibiotic‐sensitive Escherichia coli biofilm‐forming bacteria and Russian propolis ethanol extracts was evaluated. In this study, bacterial cell death occurred when the cell membranes of bacteria interacted specifically with the antibacterial compounds found in propolis. In order to understand the Russian propolis ethanol extract mechanism of action, microscopy and bacterial lysis studies were conducted. Results uncovered from these experiments imply that the mechanism of action of Russian propolis ethanol extracts is structural rather than functional. The results obtained throughout this study demonstrate cell membrane damage, resulting in cell lysis and eventually bacterial death. Significance and Impact of the Study: Most strains of bacteria and subsequently biofilms, have evolved and have altered their chemical composition in an attempt to protect themselves from antibiotics. The resistant nature of bacteria stems from the chemical rather than the physical means of inactivation of antibiotics. The results uncovered in this work demonstrate the potential application of Russian propolis ethanol extracts as a very efficient and effective method for bacterial and biofilm inactivation. Abstract : Significance and Impact of the Study: Most strains of bacteria and subsequently biofilms, have evolved and have altered their chemical composition in an attempt to protect themselves from antibiotics. The resistant nature of bacteria stems from the chemical rather than the physical means of inactivation of antibiotics. The results uncovered in this work demonstrate the potential application of Russian propolis ethanol extracts as a very efficient and effective method for bacterial and biofilm inactivation.